The Transformation of Islamic Educational Institutions in Indonesia: From Surau to Pesantren in the Digital Era - Ratu Suntiah; Susi Saadah; Darojat; Ujang Aldi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The purpose of this research is to describe the history of Islamic educational institutions in Indonesia and the innovations of these institutions in facing the development of global challenges. This research uses the library method (library research) which is only limited to library collections in the form of books and previous articles that have to do with the research title. The development of Islamic education in Indonesia is characterized by the existence of Islamic educational institutions in stages, from simple to modern stages. Among the Islamic educational institutions built and developed in Indonesia are; surau, meunasah, pesantren, and madrasah. In its history, the development of Islamic educational institutions in Indonesia has different backgrounds, styles, and roles as well as changes in line with the times.